2007
DOI: 10.1073/pnas.0700480104
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring of the dinucleotide-binding fold in an NADP(H) sensor protein

Abstract: Rossmann fold ͉ signal transduction N AD and its phosphorylated form, NADP, is a universal cofactor in a large number of redox reactions carried out by a variety of enzymes, especially dehydrogenases. It is widely recognized that NAD(P) is an essential molecule in energy metabolism in all organisms. More recently, mounting evidence suggests that, in addition to its central role in energy metabolism, NAD(P) is also involved in signaling pathways that regulate fundamental processes of cellular functions, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 35 publications
1
61
0
Order By: Relevance
“…The human protein HSCARG (NmrA-like family domaincontaining protein 1 or NMRAL1) has been identified as a novel NADPH sensor Zheng et al, 2007). Our previous studies have shown that HSCARG restructures and redistributes in response to changes of intracellular NADPH/NADP + levels Zheng et al, 2007) and found that HSCARG is involved in the regulation of nitric oxide (NO) production through repression of the activity of argininosuccinate synthetase (AS), a rate-limiting enzyme in NO synthesis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human protein HSCARG (NmrA-like family domaincontaining protein 1 or NMRAL1) has been identified as a novel NADPH sensor Zheng et al, 2007). Our previous studies have shown that HSCARG restructures and redistributes in response to changes of intracellular NADPH/NADP + levels Zheng et al, 2007) and found that HSCARG is involved in the regulation of nitric oxide (NO) production through repression of the activity of argininosuccinate synthetase (AS), a rate-limiting enzyme in NO synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that HSCARG restructures and redistributes in response to changes of intracellular NADPH/NADP + levels Zheng et al, 2007) and found that HSCARG is involved in the regulation of nitric oxide (NO) production through repression of the activity of argininosuccinate synthetase (AS), a rate-limiting enzyme in NO synthesis . The interaction between HSCARG and AS is enhanced when the intracellular NADPH/NADP + levels decreased and leads to a stronger inhibition by HSCARG on AS and NO production.…”
Section: Introductionmentioning
confidence: 99%
“…27 In this respect we note that the Human protein HSCARG, which belongs to the NmrA-like structural family, binds NADPH with a 360-fold lower K D than that for NADP þ . 15 Given these observations, a redox sensing role for NmrA is less likely.…”
Section: Discussionmentioning
confidence: 99%
“…13 HSCARG is essential for epithelial cell viability, binds NADPH much more strongly than NADP þ and may link changes in the NADP þ : NADPH ratio to modulation of the production of the important cell signaling molecule nitric oxide. [14][15][16] Microcalorimetry experiments showed that NmrA binds NAD þ and NADP þ with similar affinity but has a greatly reduced affinity for NADH and NADPH. The structure of NmrA in a complex with NADP þ has shown how repositioning a His 37 sidechain allows the different conformations of NAD þ and NADP þ to be accommodated.…”
Section: Introductionmentioning
confidence: 99%
“…It also shows close homology with UDP-galactose 4-epimerase. It is known that NmrA protein binds oxidized NAD which has probably certain regulating function (Zheng et al 2007). Its dehydrogenase and reductase activity probably does not work in this case ?…”
Section: Discussionmentioning
confidence: 99%